-(6x-3)-(5x-5)+11=-10(x-1)-(4x+9)+3

Simple and best practice solution for -(6x-3)-(5x-5)+11=-10(x-1)-(4x+9)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(6x-3)-(5x-5)+11=-10(x-1)-(4x+9)+3 equation:



-(6x-3)-(5x-5)+11=-10(x-1)-(4x+9)+3
We move all terms to the left:
-(6x-3)-(5x-5)+11-(-10(x-1)-(4x+9)+3)=0
We get rid of parentheses
-6x-5x-(-10(x-1)-(4x+9)+3)+3+5+11=0
We calculate terms in parentheses: -(-10(x-1)-(4x+9)+3), so:
-10(x-1)-(4x+9)+3
We multiply parentheses
-10x-(4x+9)+10+3
We get rid of parentheses
-10x-4x-9+10+3
We add all the numbers together, and all the variables
-14x+4
Back to the equation:
-(-14x+4)
We add all the numbers together, and all the variables
-11x-(-14x+4)+19=0
We get rid of parentheses
-11x+14x-4+19=0
We add all the numbers together, and all the variables
3x+15=0
We move all terms containing x to the left, all other terms to the right
3x=-15
x=-15/3
x=-5

See similar equations:

| (3x)^2=180 | | (X+5)+(2x+3)=8 | | y−3=−3y−43 | | 3m–7=20 | | 255=54-y | | 4.50=4x | | 3x+88=187 | | 4.50x=4 | | 3x+38=187 | | 3s+9=34 | | 2,5x^2+x+1=0 | | 0.1x-0.7(4-x)=0.8 | | 5y-9=4y | | 4.5*x=4*x | | a/4+6=-4 | | 4.50x=4x | | 3x2+7x+18=0 | | 1/8x-1=x | | 744=520+28x | | 1/4x-1=2x | | 4.50x-15000=4x-15800 | | 6x=37/39 | | 3x=36/30 | | 4+3(x–1)=2(x–2) | | 10x-5+2x=7 | | (1/4)*x-1=2x | | 1/4*x-1=2x | | x+6+x=49 | | 3y-1/2=2 | | 3*(10-4*a)+2*(7*a-4)=0 | | n*(n+1)/2=106 | | 8x+5+2x=34 |

Equations solver categories